Pengaruh Learning Capability and Integration Capability terhadap Kinerja Karyawan Perhotelan di Kota Bitung - Rorong, Arie Junus; Tumbel, Tinneke Meyske; Punuindoong, Aneke Yolly; Pombengi, Jericho Danga; Ardiyansah, Ardiyansah; Nurjaman, Nurjaman (Fakultas Ilmu Administrasi Universitas Krisnadwipayana Jakarta, 2025)
The development of business competition in Indonesia is one of the most interesting phenomena to observe, especially with the globalization in the economic sector which increasingly opens up business opportunities to compete in various business fields and industries. One of the industries affected by globalization is the service industry such as hotels, telecommunications, transportation, manufacturing and banking. This study aims to analyze and describe the effect of learning capability and integration capability on the performance of hotel employees in Bitung City. This is done to improve the performance of hotel employees which will later have an impact on improving services and increasing tourist visits to Bitung City. This study uses a quantitative approach by distributing questionnaires to hotel employees in Bitung City. Data processing and analysis are carried out using SPSS software to maintain the objectivity of the research data. The analysis used in this study is descriptive statistical analysis and hypothesis testing. The results of the study showed that the multiple correlation value was 0.745, this indicates that there is a significant positive relationship between Learning Capability and Integration Capability together on employee performance. Furthermore, from this correlation value, a determination coefficient value (R2) of 0.529 was obtained, which means that 52.9% of the employee performance variable is influenced by the Learning Capability and Integration Capability variables, the remaining 58.1% is explained by other variables.